2008
DOI: 10.1093/pubmed/fdn100
|View full text |Cite
|
Sign up to set email alerts
|

Violent behavior among adolescents in post-war Lebanon: the role of personal factors and correlation with other problem behaviors

Abstract: Compared with other countries, the rates of violent behavior in Lebanon are relatively high. The results from this study are discussed in light of the political ecology of Lebanon which may contribute to a culture that perpetrates violent behavior and may have influenced the clustering pattern of risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
5
11
1
1
Order By: Relevance
“…Violence-related behaviour (being bullied, physically attacked and participation in a physical ght) decreased in this study, which concurs with four other studies [14,[24][25][26], while a few studies found an increase in one or more types of interpersonal violence, e.g., in Oman [16], the Philippines [15] and Venezuela [27]. In several older studies among adolescents in Lebanon, high rates of interpersonal violence have been reported [5][6][7], which compares with our high rates of interpersonal violence in the 2005 GSHS. It is possible that the high rates of interpersonal violence in 2005 were still related to the post-con ict situation in Lebanon, which subsequently subsided so that interpersonal violence decreased from 2005 to 2017.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Violence-related behaviour (being bullied, physically attacked and participation in a physical ght) decreased in this study, which concurs with four other studies [14,[24][25][26], while a few studies found an increase in one or more types of interpersonal violence, e.g., in Oman [16], the Philippines [15] and Venezuela [27]. In several older studies among adolescents in Lebanon, high rates of interpersonal violence have been reported [5][6][7], which compares with our high rates of interpersonal violence in the 2005 GSHS. It is possible that the high rates of interpersonal violence in 2005 were still related to the post-con ict situation in Lebanon, which subsequently subsided so that interpersonal violence decreased from 2005 to 2017.…”
Section: Discussionsupporting
confidence: 91%
“…[3,4] Previous cross-sectional studies among adolescents in Lebanon found a high prevalence of various health risk behaviours. In terms of interpersonal violence, a high prevalence of involvement in physical ght (almost 42%) were found among school adolescents in Beirut, Lebanon [5]. In a national sample of adolescents in Lebanon in 2009, "76.4% and 81.2% of these had experienced physical and verbal/emotional abuse respectively at least once at school."…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies in that region have either focused on violent behavior (Sibai, Tohme, Beydoun, Kanaan, & Sibai, 2009) or on suicidal ideation (Mahfoud et al, 2011;Itani, Jacobsen, & Kraemer, 2017) and have yet to examine the association between polyvictimization and suicidal ideation. The current study aims at bridging the gap in the literature by exploring the latter association in the United Arab Emirates (UAE).…”
Section: Introductionmentioning
confidence: 99%
“…11 A variety of protective factors have also been identified; for example, social support buffers stressful experiences, 12 and resilience has been associated with increased well-being. 13 Coping mechanisms can also affect the impact of stress on health.…”
mentioning
confidence: 99%